Machine learning capabilities for the diagnosis of orphan diseases - N. Y. Dmitrieva (Реальная клиническая практика: данные и доказательства, 2023)
Rare or orphan diseases belong to one of the most severe groups of diseases. At the same time, early and accurate diagnosis of such diseases is a serious problem for general practitioners, pediatricians and therapists. The article discusses the possibilities of using machine learning methods, including artificial intelligence, to improve the diagnosis of rare diseases. Information is provided on various models developed by both international experts and Russian researchers.